Paper mill-based integrated nutrition of garden pea in the Eastern Himalayas - KUMAR, RAKESH; THIRUGNANAVEL, A; KUMAWAT, NARENDRA; DEKA, BIDYUT C (The Indian Journal of Agricultural Sciences, 2021)
Field experiment was conducted during rabi 2013-14 and 2014-15 to study the effect of paper mill waste integrated nutrition on yield, economics and soil health of garden pea varieties at ICAR-Research Complex for NEH Region, Nagaland Centre, Jharnapani, Nagaland. The experiment was laid out in split plot design and replicated thrice. Maximum seed yields (905 kg/ha), green pod yields (3454 kg/ha), gross return (₹ 108372/ha), net return (₹ 60260/ha) and B: C ratio (2.25) had recorded with Azad pea. Application of paper mill waste @ 1.0 t/ha gave higher yield attributes of garden pea than to its lowers levels. Highest gross return (₹109189/ha) and net return (₹ 57977/ha) was obtained with paper mill waste @ 1.0 t/ha, however the maximum B: C ratio (2.20) was noted in 0.5 t/ha. Significantly higher seed yield (926 kg/ha) and green pod yield (3449 kg/ha) were recorded with application of 100% RDF+25% RDF (ON), which was 53, 13, and 45% higher, respectively over control. Among integrated nutrition, maximum seed yield (977 kg/ha), green pod yield (3646), gross return (₹ 115328/ha), net return (₹ 64616/ha) and B:C ratio (2.28) was noted with 100% RDF + 25% RDF (ON). Soil health attributes, i.e. pH, EC, soil organic carbon; available NPK had improved significantly due to integrated nutrition. Thus, Azad pea could be grown with application of paper mill waste @ 1.0 t/ha along with 100% RDF+25% RDF(ON) for better productivity, profitability and soil health in Eastern Himalayas.